Does cervical favourability and mode of delivery affect the maternal and perinatal outcome in eclampsia?: a cohort study - Zulfeen, Momina; Tatapudi, Radha; Sowjanya, Ravella (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To study the association between cervical favorability at admission and maternal, perinatal outcome. To study the association between mode of delivery and maternal, perinatal outcome in eclampsia. Methods: This was a retrospective cohort study carried out in a tertiary hospital. All women (92) admitted with antepartum eclampsia from April 2015 to April 2016, with >32 weeks gestation, reassuring foetal heart and no other complications were included in the study. They were divided into two cohorts delivery, maternal and perinatal outcomes were compared between the two groups. Results: Group with favourable cervix achieved higher vaginal deliveries. Perinatal mortality and morbidity were significantly higher in patients with unfavourable cervix (mortality 39.6% and 20.5% respectively, p: 0.046: morbidity 25.6% and 7.8% respectively, p: 0.033), more so in vaginal delivery (RR 2.355). However there was no significant difference in maternal morbidity. Higher induction-to-delivery interval was the major contributory factor. Conclusions: Perinatal outcome was worse in patients with unfavourable cervix at induction. This can be attributed to increased induction to delivery time and vaginal route of delivery. Prolonged induction should be avoided in eclampsia.